2021
DOI: 10.46328/ijemst.1624
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students' Views of the Quality of Pedagogical Education in Russia

Abstract: All participants in educational relations are worried about the problem how to improve the quality of education, with everyone representing it through the prism of their value system. In this connection there is a need to structure these representations. It is necessary to begin with bringing into a unified system the representations of education direct customers – students. The aim of our article is to analyze how pedagogical university students perceive the quality of their education. On the basis of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Teachers' professional development activities have significant impacts school improvement as reported by scholars (Enamul, Mahabubul, Kanesean, 2011). Being student at higher educational institute students always remain conscious about quality of education required for professional life (Makarova, Ldokova & Egorova, 2021). Rivkin, Hanushek and Kain (2005) disentangled the impact of schools and instructors in influencing success of students.…”
Section: Resultsmentioning
confidence: 99%
“…Teachers' professional development activities have significant impacts school improvement as reported by scholars (Enamul, Mahabubul, Kanesean, 2011). Being student at higher educational institute students always remain conscious about quality of education required for professional life (Makarova, Ldokova & Egorova, 2021). Rivkin, Hanushek and Kain (2005) disentangled the impact of schools and instructors in influencing success of students.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, technological advancements and the increased availability of ICT resources have changed traditional learning environments: new forms of appropriation, reception, creation and the transmission of experiences and knowledge arise, boundaries between formal, non-formal and informal learning become blurred . A vast body of empirical research underlines the importance that education needs to respond to these changes (Hu, Gong, Lai, & Leung, 2018;Balsmeier & Woerter, 2019;Huang, Henfridsson, Liu, & Newell, 2017;Makarova, Ldokova, & Egorova, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To support this claim,Marpa (2021), found that the attitudes of the mathematics teachers toward using technology in terms of behavioural engagement and confidence with technology were positive while strongly positive in terms of affective engagement.Consistent withPark, Song, and Hong (2018), whose study investigated how Facebook use influences student commitment in the classroom hall, results from their examination disclosed that students with very active Facebook use accomplished fundamentally higher scores on student commitment than those with less active Facebook use. It is argued from recent literature (e.g Batmang, Sultan, Azis, & Gunawan, 2021;Çetinkaya, 2019;Kaban, 2021a;Makarova, Ldokova, & Egorova, 2021;Marpa, 2021;Shukla, & Mcinnis, 2021…”
mentioning
confidence: 99%